BEDA PENGARUH PEMBERIAN TRANSLASI OSILASI DAN THERABAND EXERCISE ATAU HOLD RELAX TERHADAP PENURUNAN NYERI DAN PENINGKATAN RANGE OF MOTION PADA PENDERITA OSTEOARHRITIS KNEE DI RUMAH SAKIT ISLAM FAISAL MAKASSAR - Mariana Ulfah; Tiar Erawan; Andi Halimah (Politeknik Kesehatan Makassar, 2021)
Background: Osteoarthritis of the knee is a degenerative joint disease that causes cartilage damage in the knee joint which is characterized by loss and erosion of the knee joint cartilage and the growth of osteophytes on the edges of the knee joint, causing stiffness, pain and impaired movement.Methods: This study was a quasi-experimental study with a pre-test post-test design with two groups aiming to determine the difference in the effect of translation oscillations and theraband exercise with translation oscillations and hold relax on pain reduction and ROM improvement in patients with knee osteoarthritis. This research was conducted at the Faisal Islamic Hospital in Makassar, with a sample of knee osteoarthritis patients who fit the inclusion criteria. The number of samples was 14 people who were randomly divided into 2 groups, namely 1 group that was given translation oscillation and theraband exercise as many as 7 people and group 2 that was given translation oscillation and hold relax as many as 7 people. Measuring instruments used are VAS and Goniometer.Results: Analysis of the paired sample t test in the treatment and control groups obtained a value of p = 0.000 <0.05 for the actuality of pain and ROM, which means that there was a significant effect in the treatment and control groups on reducing pain and increasing ROM. The results of the independent sample t test for actuality of pain obtained a value of p = 0.053 > 0.05 and for ROM obtained a value of p = 0.365 > 0.05 which means that there was no significant difference between the two sample groups.Conclusion: It can be concluded that the administration of translational oscillations and theraband exercise has no more effect than translational oscillations and hold relax on reducing pain and increasing ROM in patients with knee osteoarthritis.Keywords: Translational Oscillation, Theraband Exercise, Hold Relax, Knee Osteoarthritis